Modification of Shooting Kits to Improve Shooting Accuracy in MBO Petanque Students Muhammadiyah Surakarta University - Muhammad Hisbul Barokah; Nurhidayat (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
This study aims to determine the effect of Modified Shooting Kits on Increase Shooting in MBO Petanque UMS Students. The practice of using modified shooting kits aims to make MBO petanque when running the training program become accustomed to throwing shots on the iron. The method used in this study uses an experimental method and uses a "one group pretest posttest design" design. The test instrument uses the shooting from the FIPJP rules with stations 1,2,3,4,5 and shooting ranging from 6 meters, 7 meters, 8 meters, and 9 meters. students of MBO Petanque UMS who are the subjects of this research. In taking the sample using the purposive sampling technique. Based on the t-test conducted, the data showed that the practice using modified shooting kits had a significant value of 0.003 <0.05 so there was a significant effect of shooting using modified shooting kits accuracy shooting in MBO petanque UMS students. practice model shooting modification kits accuracy shooting of MBO petanque average of pretest average of posttest 17.60 shooting increase of 7.20 for the accuracy of the shooting game compared to before the practice.